2020
DOI: 10.22270/ujpr.v5i5.482
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of Dengue Fever Virus Among Suspected Patients in Taiz Governorate-Yemen

Abstract: Background: Dengue Fever virus (DENV) considers one of the most important mosquito-borne viral diseases in the world and it is endemic in more than 100 countries. Objective: This study aimed to determine the seroprevalence of DENV infection among suspected patients and to investigate some associated risk factors with dengue fever infection in Taiz governorate, Yemen. Methods: This study was cross-sectional, descriptive, and experimental, combining the use of a structured questionnaire and analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

5
2

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 11 publications
1
6
0
Order By: Relevance
“…In the current work, it was found that the age group of 16-30 years old was the most infected by DF than other age groups. This finding is in agreement with the result by Abdullah et al, 11 who found that the age group of 21-30 years the most susceptible for DF than other age groups. Similar findings were also supported with previous reports that observed that the age group of 20-45 years were more exposed to 14,15,16,17,18 .…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…In the current work, it was found that the age group of 16-30 years old was the most infected by DF than other age groups. This finding is in agreement with the result by Abdullah et al, 11 who found that the age group of 21-30 years the most susceptible for DF than other age groups. Similar findings were also supported with previous reports that observed that the age group of 20-45 years were more exposed to 14,15,16,17,18 .…”
Section: Discussionsupporting
confidence: 94%
“…The present result revealed that the highest prevalence of DF was (73.1%) more among when compared with females (26.09%). In a similar study by Abdullah et al, 11 who found that 67.3% of cases were males and 32.7% were females in Taiz, Yemen. Also, several reports that were carried out in some regions in Yemen documented that males were more affected by fever infection than females 13,14,15 .…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…In addition medical waste handlers were infected by HBsAg (20.4%) in Ethiopia 1 , HBsAg (1.3%) and HCV (0.7%) in southern Ethiopia 16 , HBsAg (2.3%) and HCV (2.7%) in Tripoli, Libya 15 , 1.59% for HBsAg in Palestine 17 , 6.3% for HBV and 1% for HCV in Bangladesh 18 , and HIV (5%) in Africa 19 . Yemen is one of the developing countries where the infectious pathogenic microorganisms are easily spread among the population due to the lack of an effective health system, unsafe drinking water, poor environmental sensation, and uncontrolled disease transmission [20][21][22][23][24][25] . The prevalence rate of positive anti-HB core antibody among the population was between 8-50% in 2000 by Al-Shamahy 26 and between 20% by Sallam et al, 26 .…”
Section: Introductionmentioning
confidence: 99%